New Music and Institutional Critique - Grüny, Christian; Farnsworth, Brandon (Ästhetiken X.0 - Zeitgenössische Konturen ästhetischen Denkens,, 2024)
While institutional critique remains a significant part of artistic practice and theoretical debate in the arts, its has long escaped scholarly attention in the field of music. This open access volume assembles for the first time an array of theoretical approaches and practical examples dealing with New Music's institutions, their critique, and their transformations. For researchers, leaders, and practitioners alike, it offers an important overview of current developments as well as theoretical reflections about New Music and its institutions today.